Interpretation of Religious Texts and Its Impact on Coexistence with Others - Alsaied, Mohamad Abdullah; Almheiri, Mohamed Ghanem (Journal of Posthumanism, 2025)
The interpretation of religious texts is a fundamental issue affecting societal coexistence. This research was undertaken to explore how a comparative hermeneutical analysis of Western religious texts and the Quran can reveal differences in interpretative traditions and assess their impact on intercultural understanding. A close textual analysis was employed to examine key interpretative traditions, analyzing the historical and conceptual evolution of ta’wil and tafsir. Comparative methods were used to review Western hermeneutics alongside Islamic approaches. The study found that interpretation plays a crucial role in shaping relationships between cultures and religions. It revealed clear, objective differences between Western and Islamic interpretations and showed that an open and balanced approach to the Quran can enhance mutual understanding and tolerance. The findings suggest that adopting an interpretative framework that respects both traditional and modern critical methods can build bridges of communication and promote coexistence. Recommendations include fostering interdisciplinary dialogue to refine interpretative practices in religious studies.